2019
DOI: 10.1038/s41598-019-43615-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytological adequacy and pain scale score in ultrasound-guided fine-needle aspiration of solid thyroid nodules for liquid-based cytology with with 23- and 25-gauge needles: a single-center prospective study

Abstract: In ultrasound (US)-guided fine-needle aspiration (FNA) of solid thyroid nodules (STN) using liquid-based cytology (LBC), the most appropriate needle size for LBC remains unclear. This study compared the cytological adequacy and complications associated with using 23- and 25-gauge needles in US-guided FNA of STNs using LBC. US-guided FNA was performed in consecutive patients by one radiologist to diagnose STNs ≥ 5 mm in the largest diameter. The one-sampling technique through a single needle puncture and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…Thyroid nodules with high inadequate risk have a significantly higher inadequate rate after US-FNA in our study, comparing with the overall 3748 nodules in our center (16.7% vs. 6.6%, P < 0.001) or some other centers [ 17 ]. They have some common US features, such as high cystic composition, mixed cystic and solid nodules with hemorrhage, or suspicious degenerating nodules [ 4 , 6 ].…”
Section: Discussionsupporting
confidence: 58%
“…Thyroid nodules with high inadequate risk have a significantly higher inadequate rate after US-FNA in our study, comparing with the overall 3748 nodules in our center (16.7% vs. 6.6%, P < 0.001) or some other centers [ 17 ]. They have some common US features, such as high cystic composition, mixed cystic and solid nodules with hemorrhage, or suspicious degenerating nodules [ 4 , 6 ].…”
Section: Discussionsupporting
confidence: 58%
“…The selection of needle is an essential technical element of fine needle biopsy. Needle gauge is an important factor that is affecting results of both conventional smear cytology and liquid-based cytology [ 4 , 7 , 9 , 15 ]. In this paper, we objectively investigate the effect of needle gauge on specimen quality during USG-FNB, including FNC and FNA.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of clinical use, thinner needles were recommended as a priority in order to reduce complications, as studies have found that larger needle injured thyroid gland severer than thinner one [7,8]. Moreover, smaller needles used in punctuation were more tolerable psychologically for patients, although previous studies found that there was no difference in pain scale of punctuation using different caliber of needle [2,15,22].…”
Section: Discussionmentioning
confidence: 99%
“…As noted in this study the discomfort experienced with fine needle aspiration is mild in the majority of patients. The use of local injected anesthetic in these patients was not associated with a reduction in FNA related discomfort and in light of the pain associated with lidocaine injection, does not seem to add any benefit in lowering overall discomfort experienced during a thyroid FNA procedure (7)(8)(9)20).…”
Section: Discussionmentioning
confidence: 76%
“…As FNA is performed by percutaneous puncture, some discomfort is typically associated with the procedure. The needle size, thyroid nodule size or depth, number of passes, physician's expertise, and technique used have not been demonstrated to contribute to increased discomfort during or after this procedure (20)(21)(22). A limited amount of research has found that age < 25 years old, female gender, anxiety, perpendicular technique, greater thyroid nodule depth and large needle gauge may associated with increased FNA related discomfort (8,(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%